The Anatomy of Industry R&D Intensity Distributions - Cohen, Wesley M.; Klepper, Steven (American Economic Review, 2016)
Using firm data disaggregated by industry, the authors establish a set of regularities in the distribution of firm R&D intensities within manufacturing industries. The authors show how a simple probabilistic process, in which change influences a key unobserved determinant of R&D and firm size conditions the returns to R&D, can account for these regularities and other features of the distributions. The model provides a unified, noncausal explanation of a series of long-observed relationships across mean R&D intensity, market concentration, and the coefficient of variation. It also offers a novel explanation for the inverse relationship between R&D productivity and firm size. Copyright 1992 by American Economic Association.